A deep dive into CDK4/6 inhibitors: Evaluating real world toxicities and treatment paradigms in the elderly population. (January 2023) - Olazagasti, Coral; Lee, Chung-Shien; Liu, Angel; Stefanov, Dimitre; Cheng, Kit
Background: Cyclin-dependent kinase 4/6 inhibitors have become part of the standard of care in the treatment of hormone receptor positive, Her2Neu negative metastatic breast cancer. There is concern regarding the efficacy and potential increased cyclin-dependent kinase 4/6 inhibitors toxicity in the geriatric population in the community compared to the clinical trial population. Methods: We evaluated patients treated with cyclin-dependent kinase 4/6 inhibitors from 2015 to 2019 and stratified according to age ≥70 and <70 years. Complete blood count from the first two cycles was recorded. Rates of hematologic toxicities, dose interruptions and reductions, progression-free survival, and overall survival were compared between both groups. We sought to assess the hematologic toxicities between the age groups and the relationship between previous chemotherapy exposure, bone metastasis and starting cyclin-dependent kinase 4/6 inhibitors dose with progression-free survival and overall survival. Results: A total of 202 patients were included, 73 were ≥70 years and 129 were <70 years of age. There was no association between age group and grade of neutropenia or thrombocytopenia. There was a profound association between progression-free survival and overall survival and starting dose, where patients with recommended starting dose had higher progression-free survival and overall survival than those with a reduced dose ( p = 0.0003 and p = 0.04). Conclusions: Our study showed similar progression-free survival and overall survival between age groups without significant differences in neutropenia or thrombocytopenia toxicity. Nevertheless, we found an association between starting dose and progression-free survival and overall survival that has not been previously reported. Given the good tolerability across age groups and the improvement in progression-free survival and overall survival, patients should be treated at the cyclin-dependent kinase 4/6 inhibitors recommended dose and monitored appropriately.